The Filipino family as described and prescribed by law preliminary findings of a study on family policy - Cariño, Ledivina V. (1991)
The family is recognized as the basic foundation of the Filipino nation, thus, policies which have direct and indirect implications to it, abound. Family policies are operationalized in the Philippine Constitution, Family Code, Child and Youth Welfare Code, laws on family planning, labor, social security, health, taxation, civil service and other issues of public concern. There are four classifications of special families specifically dealt with by the state. These are the low-income families, the families of veterans, Muslim families and the families of those in public service. Filipino families play a great role in Philippine society either as major instruments or beneficiaries of state policies. However, the efficiency of the instruments of the state coupled with the complexity and sanctity of family arrangements sometimes limit the state in pursuing its desired goals.
Keywords: Family policy; Domestic relations; Families